2007
DOI: 10.7202/016193ar
|View full text |Cite
|
Sign up to set email alerts
|

La composante parentale d’un programme d’éveil numérique destiné aux enfants de milieu socioéconomiquement faible du niveau de la maternelle représente-t-elle une valeur ajoutée ?

Abstract: Cette étude a pour but d’évaluer l’impact à court terme d’un volet parental inhérent à un programme d’éveil numérique offert à la maternelle aux enfants de milieu socioéconomiquement faible. Nos résultats indiquent que la participation conjointe des parents et des enfants dans le programme (groupe expérimental) semble avoir favorisé, chez les enfants, une meilleure connaissance des nombres comparativement aux enfants n’ayant bénéficié que du volet enfant. Des résultats peu concluants ont néanmoins été observés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
(67 reference statements)
0
0
0
Order By: Relevance
“…This reveals that the home-based intervention as was implemented here prompted parents who are not the closest to the school culture to get involved. By contrast, some studies where the home-based intervention group were the families who had responded to an invitation or participated in training sessions have found that the home-based group was socio-economically more advantaged than the other groups (Farrell, 2014;Jalbert & Pagani, 2007;Niklas et al, 2016;Sonnenschein et al, 2016). Recruiting more advantaged families not only raises ethical but also methodological questions, since the socioeconomic index is a moderator of the intervention's effects (Dulay et al, 2018;Manz, Hughes, Barnabas, Bracaliello, & Ginsburg-Block, 2010).…”
Section: Kindergarten and Home-based Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…This reveals that the home-based intervention as was implemented here prompted parents who are not the closest to the school culture to get involved. By contrast, some studies where the home-based intervention group were the families who had responded to an invitation or participated in training sessions have found that the home-based group was socio-economically more advantaged than the other groups (Farrell, 2014;Jalbert & Pagani, 2007;Niklas et al, 2016;Sonnenschein et al, 2016). Recruiting more advantaged families not only raises ethical but also methodological questions, since the socioeconomic index is a moderator of the intervention's effects (Dulay et al, 2018;Manz, Hughes, Barnabas, Bracaliello, & Ginsburg-Block, 2010).…”
Section: Kindergarten and Home-based Interventionmentioning
confidence: 99%
“…According to our review of the literature, only one study published in French has measured the added value of having parents participate in a kindergarten intervention relative to a mathematical intervention implemented only at kindergarten (Jalbert & Pagani, 2007). In this study (Rightstart program), parents participated in four training workshops, half of them with their child.…”
Section: Early Number Skills At Homementioning
confidence: 99%
See 1 more Smart Citation